2023
DOI: 10.1037/emo0001135
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in inhibitory control are not related to downregulation of negative emotion via distancing.

Abstract: Evidence suggests that cognitive control and emotional control share partly the same cognitive processes. For example, downregulation of negative emotions requires inhibiting or limiting the expression of a prepotent appraisal of a situation in favor of selecting an alternative appraisal. Although inhibitory control seems to be a particularly relevant process in emotion regulation (ER), previous studies reported inconsistent findings on their relationship, likely because of the application of single task measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 115 publications
1
8
0
Order By: Relevance
“…In addition, the levator labii superioris (associated with disgust) has also been associated with reduced activity during reappraisal 6 . Similar effects have been reported for suppression 6 , distancing 7 , and distraction 8 . Importantly, results on electromyographic measures seem to be more consistent compared to other autonomic measures, likely because they are specific to emotional valence and its changes.…”
Section: Introductionsupporting
confidence: 83%
“…In addition, the levator labii superioris (associated with disgust) has also been associated with reduced activity during reappraisal 6 . Similar effects have been reported for suppression 6 , distancing 7 , and distraction 8 . Importantly, results on electromyographic measures seem to be more consistent compared to other autonomic measures, likely because they are specific to emotional valence and its changes.…”
Section: Introductionsupporting
confidence: 83%
“…It may also stimulate debate on whether the failure to observe a relationship is an artefact of research design or a genuine psychological phenomenon. The study by Gärtner et al (2022) presents an important insight in this matter. In their study, a very thoroughly assessment was conducted on inhibitory control and emotion regulation.…”
Section: Discussionmentioning
confidence: 93%
“…Research exploring the role of inhibitory control in emotional regulation has yielded surprisingly inconclusive results (e.g., McRae et al, 2012 ; Beauchamp et al, 2016 ; Hendricks and Buchanan, 2016 ; Sperduti et al, 2017 ). For example, a study by Gärtner et al (2022) conducted an exhaustive assessment of inhibitory control, generating a latent score based on six different experimental tasks focused on this cognitive function. Concurrently, emotion regulation was evaluated through a combination of self-report instruments and psychophysiological markers.…”
Section: Introductionmentioning
confidence: 99%
“…Effect sizes for facial EMG modulations are usually medium during emotion regulation (Zaehringer et al, 2020) and medium to large when investigating effects of emotional valence (e.g., Dan-Glauser & Gross, 2011;Gärtner et al, 2022), indicating good group-level precision of EMG measures. Furthermore, psychometric properties are generally good (Kaye et al, 2016) and because of good signal-to-noise ratio for the startle blink reflex, responses can also be analyzed at the single-trial level (e.g., Mueller et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is necessary to investigate whether the assessment of different muscles or multiple muscle sites (e.g., laterality) provides better precision and incremental predictive validity with respect to the measurement of emotional states (e.g., Gärtner et al, 2022, found no differences between recording sites).…”
Section: Design and Data Collectionmentioning
confidence: 99%